PENGARUH PENGGUNAAN MODUL HASIL PENELITIAN BENTOS PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS X SMA NEGERI 1 MOJOLABAN TAHUN PELAJARAN 2011/2012 - Wibowo, Pandu Haryo; Indrowati, Meti; Sugiharto, Bowo (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? The purposes of this research ware to ascertain the influence of implementation bentos research result module in subject of environmental polution towards students science process skill of tenth grade students of SMA Negeri 1 Mojolaban in the academic year 2011/2012. This research is considered as quasi experiment research using quantitative approach. The research was designed using posttest only control design that applied bentos research result module in subject of environmental polution approach in experimental group and conventional approach method in control group. The population of this research was all of X degree students at SMA Negeri 1 Mojolaban in the academic year 2011/2012. The sample of this research was established by cluster random sampling that choosed X.5 as experiment group and X.6 as control group. The data was collected by using essay test, observation form, and document. The hypotheses analyzed by t-test. The conclusion result obtained using t-test are value for 0.004, so the probabilitas significance (p-value) < 0.05, thus received H1 and HO rejected. It means there is a significant difference of implementation bentos research result module in subject of environmental polution in class experiment and conventional approach method in class control towards students science process skill. The conclusion of this research showed that application of implementation bentos research result module in subject of environmental pollution had significant effect towards students science process skill of tenth grade students of SMA Negeri 1 Mojolaban in the academic year 2011/2012. Keywords: Module, Sains Proces Skill.